2015
DOI: 10.1155/2015/325061
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Palmitoylethanolamide on Expressive Language, Cognition, and Behaviors in Autism: A Report of Two Cases

Abstract: Introduction. Autism spectrum disorders are defined by behavioral and language atypias. Growing body of evidence indicates inflammatory mediators may contribute to the condition. Palmitoylethanolamide (PEA) is naturally occurring and has been available as a nonprescription medical food supplement in Europe since 2008. PEA has been tested in thousands of human subjects without any noted significant side effects. Here we report the first cases of the administration of PEA to two children with autism. Case Presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 29 publications
3
40
0
Order By: Relevance
“…In the described case report, chronic co-ultraPEA-LUTâ reduced behavioral alterations of a child with ASD. Our observations are consistent with the results obtained after treatment with ultramicronized PEA, administered alone, in two children suffering from autism spectrum disorder [59]. It is important to point out that children with autism experience a higher incidence of anxiety, particularly social anxiety, than children with other developmental disorders or with a normal development [60].…”
Section: Hippocampus Cerebellumsupporting
confidence: 90%
“…In the described case report, chronic co-ultraPEA-LUTâ reduced behavioral alterations of a child with ASD. Our observations are consistent with the results obtained after treatment with ultramicronized PEA, administered alone, in two children suffering from autism spectrum disorder [59]. It is important to point out that children with autism experience a higher incidence of anxiety, particularly social anxiety, than children with other developmental disorders or with a normal development [60].…”
Section: Hippocampus Cerebellumsupporting
confidence: 90%
“…At the Biomedical Centre for Autism Research and Treatment, several therapeutic strategies targeting the immune system and neuro-inflammation have been implemented over the course of the years (Antonucci et al, 2015). In the recent past, we focused our attention on the role of modulators of the immune system as potential candidates for ASD treatment based on the seminal work by Bradstreet et al (2012) on the Gc protein-derived Macrophage Activating Factor (GcMAF).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Kelly [27] demonstrated that plasma eCBs levels were dysregulated at age one in children with poor communication scores at age three, which implicating eCBs may be potential biomarker for early diagnosis of ASD. Anecdotally, case reports from Italy rstly have corroborated that PEA, alone or combination with other natural supplements, can re ne ASD core impairments [28]. Subsequently, an Iranian randomized, double-blind placebo-controlled trial revealed that PEA (600 mg twice daily) may augment therapeutic effects of risperidone on ASD-related irritability and hyperactivity without serious side effects [29].…”
Section: Discussionmentioning
confidence: 99%